THE EFFECT OF BUDGET IMPLEMENTATION, HUMAN RESOURCE COMPETENCE, AND INTERNAL CONTROL SYSTEM ON BUDGET ABSORPTION WITH ORGANIZATIONAL COMMITMENT AS A MODERATOR IN THE SUPREME COURT OF THE REPUBLIC OF INDONESIA Susi karyawati1 ; Suratno2; Darmansyah3 - Susi Karyawati; Suratno, Suratno; Darmansyah, Darmansyah (International Journal of Social Science, 2025)
The purpose of this study is to examine and analyze whether Budget Implementation, Human Resource Competence, and Internal Control System directly influence Budget Absorption at the Supreme Court of the Republic of Indonesia. Additionally, it seeks to test whether Organizational Commitment can moderate the relationships between the three independent variables and Budget Absorption. This study employs a descriptive quantitative approach with a confirmatory nature. The population includes all employees in the Supreme Court during 2023, with a research sample comprising 230 respondent selected using probability sampling techniques. The results reveal that Budget Implementation, Human Resource Competence, and Internal Control System have a significant positive effect on Budget Absorption. Organizational Commitment does not moderate the relationship between Budget Implementation and Budget Absorption. However, Organizational Commitment plays a role in moderating the relationships between Human Resource Competence and Internal Control System with Budget Absorption at the Supreme Court. The contribution of this research highlights that Budget Absorption can be optimized when budget implementation is conducted transparently, human resource competence is enhanced, and the internal control system is effectively executed. Furthermore, organizational commitment to governance must function properly and equitably.